2007
DOI: 10.1158/1055-9965.epi-07-0601
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Products, Calcium Intake, and Risk of Prostate Cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: Higher intakes of calcium and dairy products, a major source of dietary calcium, are reported to increase the risk of prostate cancer, potentially due to reductions in circulating vitamin D with increasing calcium intake. We prospectively examined the association of dairy product and calcium intake with prostate cancer risk in 29,509 men, including 1,910 cases, in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. We also evaluated the relation of calcium intake with serum, in a Prostate, Lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 35 publications
7
84
1
1
Order By: Relevance
“…However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007). It has been suggested that a high calcium intake may increase risk by suppressing the synthesis of 1,25-dihydroxyvitamin D, which has an antitumour effect on human prostatic cells in vitro (Giovannucci, 1998).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk. An alternative hypothesis is that dairy products may increase prostate cancer risk via their high calcium content, and our finding of a positive association with calcium intake is consistent with some (Chan et al, 2001;Gao et al, 2005;Tseng et al, 2005;Giovannucci et al, 2006;Kesse et al, 2006;Ahn et al, 2007;Mitrou et al, 2007), but not all, prospective studies (Koh et al, 2006;Severi et al, 2006;Rohrmann et al, 2007). It has been suggested that a high calcium intake may increase risk by suppressing the synthesis of 1,25-dihydroxyvitamin D, which has an antitumour effect on human prostatic cells in vitro (Giovannucci, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…In the current study, although these associations were slightly stronger for high-grade disease and for men recruited before the age of 60 years, the differences between the groups were not significant, and there were no comparable differences between localised and advanced-stage disease. Several previous studies have found that risk is particularly elevated in men with a total calcium intake (i.e., diet plus supplement intake) above 2 g day À1 (Rodriguez et al, 2003;Giovannucci et al, 2006;Ahn et al, 2007;Mitrou et al, 2007). However, we had no information on supplement use and although the present study found a significantly elevated risk in the top fifth of dietary intake, the mean intake of this category, based on 24-h recall data, was 1.3 g day À1 ; less than 1% of the cohort had a dietary calcium intake of 2 g day À1 or more.…”
Section: Discussionmentioning
confidence: 99%
“…Newly diagnosed prostate 99 of a 40% risk reduction with 4600 IU of supplemental vitamin D intake compared with men not using supplements may suggest that dietary intake of vitamin D needs to be higher than the current dietary reference intake to be protective. The current dietary reference intakes are set based on the assumption that some of our need for vitamin D can be met with sun/UVB exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary vitamin D was not associated with prostate cancer; however, risk tends to decrease with greater vitamin D from supplemental sources, with a 40% reduction in men who used 4600 IU of supplemental vitamin D compared with men not using vitamin D supplements. 99 Another study analyzed 454 male participants in the Baltimore Longitudinal Study of Aging who were 46-92 years old at the time of completion of a food frequency questionnaire. The adjusted odds ratio (OR) of prostate cancer for the highest tertile compared with that for the lowest tertile of vitamin D was 1.21 (95% CI ¼ 0.64-2.30; P-trend ¼ 0.46).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…63 However, a recent analysis of a US cohort of over 29,000 men, including 1,910 with prostate cancer, reported an association with dairy product and dietary calcium intake for nonaggressive disease only, and not for aggressive prostate cancer. 64 Aspirin and calcium are currently the only agents that have shown consistent chemopreventive activity against colorectal neoplasia in randomized trials; however, not all individuals benefit from these interventions and some experience side effects. 58,65,66 On the basis of the inverse relationship observed in our study and similar associations reported in epidemiological studies, we believe that dairy products, and more specifically milk, may have value as chemopreventive agents, making a randomized trial for CRA recurrence prevention an attractive proposition.…”
Section: Discussionmentioning
confidence: 99%